Identifikasi Mikoriza Vesikular Arbuskular (MVA) pada Rhizosfer Tanaman Ubi Jalar (Ipomoea batatas L.) dan Ubi Kayu (Manihot esculenta Crantz) serta Perbanyakannya dengan Media Zeolit - WIDIATMA, PUTU SENA; WIRAWAN, I GEDE PUTU; SUSRAMA, I GEDE KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Vesicular Arbucular Mycorrhizae (VAM) Identification of Sweet Potato ( Ipomoea batatas L.) and Cassava ( Manihot esculenta Crantz) Rhizosphere and Its Spore Multiplication in Zeolite Media Vesicular arbuscular mycorrhizae is an obligate symbiont that live in a symbiotic mutualism with plant roots and grow inside root cortical cells helping absorption of nutrients which necessary for plant growth. This research aimed to determine VAM species in sweet potato and cassava rhizosphere and also to determine effectiveness of zeolite media as a multiplication medium. The research has been conducted from October 2014 through December 2014. Spore isolation was done by conducting wet sieving method. Roots colonization percentages were calculated with gridline section method and spores multiplication through trapping culture method. Results showed that there were four VAM genera consist of 16 species from rhizosphere of both sample plants. Those four genera identified as Acaulospora (2 species), Gigaspora (1 species), Glomus (1 species), and Scutellospora (1 species) from rhizosphere of sweet potato and 3 genera identified as Acaulospora (3 species), Gigaspora (3 species), and Glomus (5 species) from rhizosphere of cassava. Colonization is characterized by special structure of VAM such as arbucule and vesicule in plant roots tissue. Inner spores of VAM were discovered in all three kind of plants used in this research. Spore multiplication with trapping culture method using zeolite media and corn as a symbionts can be considered as an effective method for VAM spore multiplication indicated by density increase of VAM spores. Keywords : Colonization, Cortical Cell, Inner Spore, Symbiont, Trapping Culture